2012
DOI: 10.1007/978-3-642-33250-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Using Online Carbon Calculators for Participation in Local Climate Initiatives

Abstract: Abstract. The paper reviews various eco-feedback systems including carbon calculators and discusses how different disciplinary approaches conceptualise and explain anticipated impacts of these systems. The European collaborative research project e2democracy investigates how citizen participation combined with long-term CO 2 monitoring and feedback can contribute to achieve local climate targets. Empirical results from local climate initiatives in Austria, Germany and Spain show positive effects in terms of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…While technology can be used to influence human behaviour and thinking [15] and to promote sustainable behaviour [16], little is known about the behavioural effects of ecological footprint calculators. Calculator users have reported that the tools increased their knowledge and awareness about their climate impact and ways to reduce it [17][18][19][20][21], and also increased their motivation to reduce their footprint [22].…”
Section: Effects Of Ecological Footprint Calculators On Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…While technology can be used to influence human behaviour and thinking [15] and to promote sustainable behaviour [16], little is known about the behavioural effects of ecological footprint calculators. Calculator users have reported that the tools increased their knowledge and awareness about their climate impact and ways to reduce it [17][18][19][20][21], and also increased their motivation to reduce their footprint [22].…”
Section: Effects Of Ecological Footprint Calculators On Behaviourmentioning
confidence: 99%
“…Students who completed a carbon footprint calculator in combination with focus group discussions also reported to have made some small changes to their lifestyle as a result [18], and students who used a carbon footprint management system (including various persuasive techniques) on a weekly basis showed reduced carbon emissions after four and six weeks [29]. Finally, a long-term study where a bi-monthly carbon calculator was used as part of a local climate initiative found that the initiative had reduced participants' CO2 emissions [19].…”
Section: Effects Of Ecological Footprint Calculators On Behaviourmentioning
confidence: 99%
“…There are only few studies on the effectiveness of using carbon calculators, and their results are mixed. Some studies have reported actual reductions amongst their participants, e.g., [27,28]. However, others have questioned whether carbon calculators really have an effect on people's behaviour.…”
Section: The Design and Use Of Carbon Footprint Calculatorsmentioning
confidence: 99%
“…This social feature connects to several other social aspects of motivation and behavioural change such as norm activation, feelings of pride and guilt, peer pressure, and so on. While several studies with limited results have been conducted on carbon calculators in the past (e.g., [6,[27][28][29]), this social setting is a rather unexplored area of carbon calculators (see [27]), which has some potential.…”
Section: Recommendationsmentioning
confidence: 99%
“…This is due both to empirical difficulties in identifying these effects and the complex relationship between politics and a continuously evolving technology. There is an urgent call in the literature for empirical data that can support the normative speculation regarding the role of cyber citizenship (Aichholzer and Allhutter, 2011).…”
Section: Introductionmentioning
confidence: 99%